Plant growth-promoting actinobacteria: a new strategy for enhancing sustainable production and protection of grain legumes - Sathya, Arumugam (3 Biotech, 2017)
Grain legumes are a cost-effective alternative for the animal protein in improving the diets of the poor in South-East Asia and Africa. Legumes, through symbiotic nitrogen fixation, meet a major part of their own N demand and partially benefit the following crops of the system by enriching soil. In realization of this sustainability advantage and to promote pulse production, United Nations had declared 2016 as the “International Year of pulses”. Grain legumes are frequently subjected to both abiotic and biotic stresses resulting in severe yield losses. Global yields of legumes have been stagnant for the past five decades in spite of adopting various conventional and molecular breeding approaches. Furthermore, the increasing costs and negative effects of pesticides and fertilizers for crop production necessitate the use of biological options of crop production and protection. The use of plant growth-promoting (PGP) bacteria for improving soil and plant health has become one of the attractive strategies for developing sustainable agricultural systems due to their eco-friendliness, low production cost and minimizing consumption of non-renewable resources. This review emphasizes on how the PGP actinobacteria and their metabolites can be used effectively in enhancing the yield and controlling the pests and pathogens of grain legumes.